WOMEN'S FIQH AS A FOUNDATION FOR ISLAMIC DA'WAH AND A DRIVER OF WOMEN'S EMPOWERMENT TO ENHANCE RELIGIOUS AWARENESS IN INDONESIA - Husna, Faiqoh; Arsam, Hawasi; Abdurrachman, Solahuddin (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
Women's fiqh is an important aspect of Islam that has great potential to empower women and enhance religious awareness in Indonesia. However, the understanding and application of women's fiqh in the context of da'wah are still suboptimal. This research aims to explore the role of women's fiqh as a foundation for Islamic da'wah and a driver of women's empowerment in Indonesia. This study employs a qualitative approach, collecting data through in-depth interviews, observations, and document analysis. The subjects of the research consist of women involved in da'wah activities and fiqh education in various institutions. The findings indicate that women's fiqh can enhance religious awareness and empower women, but there are still gaps in the application of da'wah materials relevant to contemporary challenges. The study concludes that women's fiqh has significant potential in women's empowerment, and there is a need for the development of more contextual and applicable da'wah materials. This research contributes to the understanding of women's fiqh as a tool for women's empowerment and opens up space for further discussion on the integration of fiqh in education and da'wah.